Final analysis of a Multicenter Single-Arm Confirmatory Trial of hypofractionated whole breast irradiation after breast-conserving surgery in Japan: JCOG0906. (17th March 2021) - Nozaki, Miwako; Kagami, Yoshikazu; Machida, Ryunosuke; Nakamura, Kenichi; Ito, Yoshinori; Nishimura, Yasumasa; Teshima, Teruki; Saito, Yoshihiro; Nagata, Yasushi; Matsumoto, Yasuo; Akimoto, Tetsuo; Hiraoka, Masahiro; et al.
Abstract: Objective: To evaluate the safety and efficacy of hypofractionated whole breast irradiation for Asian women after breast-conserving surgery. This is an updated report with 5-year follow-up. Methods and materials: Asian women who had invasive breast cancer with clinical tumor size ≤3 cm, pN0-1c and negative inked margins were enrolled. Hypofractionated whole breast irradiation of 42.56 Gy/16 fractions was delivered, and boost irradiation of 10.64 Gy/4 fractions was added when the surgical margin was ≤5 mm. The primary endpoint was the proportion of grade ≥ 2 late adverse reactions within 3 years. Secondary endpoints included early adverse events, overall survival, disease-free survival, ipsilateral breast relapse-free survival, late adverse reactions and cosmetic outcome. Toxicities were evaluated using CTCAE ver3.0. Cosmetic outcomes were assessed using a 4-point scale and CTCAE ver3.0 for hyper/hypopigmentation, breast nipple/areolar deformity and breast volume/deformity. Results: Between February 2010 and August 2012, 312 patients were enrolled, and 306 received hypofractionated whole breast irradiation. Median follow-up was 70.5 (range 7.6–88.9) months. The proportion of grade ≥ 2 late adverse reactions within 3 years was 4.3% (90% confidence interval 2.5–6.7%). Grade 2 early adverse events occurred in 38 (12.4%); none had grade 3/4. Five-year overall survival, disease-free survival and ipsilateral breast relapse-free survival were 98.7, 95.4 and 98.0%, respectively. Of the 304 evaluable patients, 29 (9.5%; 95% confidence interval 6.5–13.4%) had grade 2/3 late adverse reactions; none had grade 4/5. At 5 years, 70/289 (24.2%) showed any worsening of breast cosmetic changes. Conclusions: Hypofractionated whole breast irradiation is considered a standard treatment for Asian women with margin-negative invasive breast cancer after breast-conserving surgery. Abstract : A Japanese Confirmatory Trial of hypofractionated whole breast irradiation (JCOG0906) showed that hypofractionated whole breast irradiation of 42.56 Gy/16 fractions is considered a standard treatment for Asian women with margin-negative invasive breast cancer after breast-conserving surgery.